Success Test Of Growing Two Kanari Provenans (Canarium Amboinensis) At The Beginning Of Planting - Febian Filiph Tetelay; Yulianus Dominggus Komul (Universitas Lambung Mangkurat, 2023)
Research on provenance is one of the studies in the field of tree or forestry plant breeding which aims to determine the adaptability of one seed origin to the conditions in which it grows and the superiority of the provenance. Provenance test is important to determine the origin of quality forestry plant seeds, in this case the selected species is Kenari (Canarium amboinensis). In addition, the development of this species in the future uses seeds that come from quality seed sources. This study aims to determine the growth variations of two provenances of walnut (Canarium amboinensis) from Ambon and Seram islands. This research took place in April 2023 and was carried out at the Provenans Nursery of Kenari plants (Canarium amboinensis), which were 5 months old in Hatusua Village, Kairatu District, West Seram Regency. The results showed that of the 20 walnut seedlings in the provenance from Refinery Village, only 19 plants were alive and 1 plant was dead, so the percentage of survivors in walnut plants from Refinery Village was 95%. Meanwhile for Nikulukan Village, it was shown that of the 20 plants that should have existed, 17 plants were alive and 3 plants were dead, so the percentage of survival from the Kenari seedlings from provenance in Nikulukan Village was 85%. the results of the analysis above, t-count = -3.22 and when compared with t-table at α = 0.05 and degrees of freedom (db) = 35 is 2.03 then the absolute value of t-count is more than t-table so there is difference in the number of leaves of this plant in the two provenances